في ظـل التـاريخ إعادة كتابة التاريخ في رواية: " بعيدا من المدينة " لآسيا جبار - راشــدي, حسـان (قــــــراءات; No 07-06 (2014): (مجلة قراءات( نوفمبر, 2019)
تتناول هذه الدراسة نصا سرديا جزائريا مكتوبا بلغة الآخر لآسيا جبار هو: "بعيدا من المدينة loin de midine". نص يستثمر التاريخ في إنتاج الكتابة وهو يعبر عن عهد ذهبي عهد الرسول صلى الله عليه وسلم، ويرسم بغض الفجوات أو بعض الانحرافات التي حدثت بعد ذلك العهد، وكانت آثاره سلبية على المرأة بصفة خاصة إذ أغلب شخصيات هذا النص نساء تعرضن للقهر والسبي والاغتصاب. وتتساءل هذه الدراسة هل هذا النص "loi de midine" نص سردي وكفى؟ أم هو نص مؤسس يدخل في النصوص المستقبلية. Abstract: The present study deals with Asia Djebbar’s “loin de midine” (far from the midine), which is an Algerian narrative text written in a foreign language. It is a text that explores history in writing production. It mainly addresses a golden Islamic era (the era of prophet Mohammed, Peace be upon him). It portrays some of the gaps and divergences that took place during that period and its negative consequences especially on woman. Many of the characters in the story are women who had been depressed, captured and raped. This study inquires: is “loin de midine” a mere narrative text? Or can it be considered among futuristic texts?